Relationship Of Adolescent Women's Knowledge About Menarche - Anggina, Linni (Benih : Journal of Midwifery, 2023)
Menarche is the first menstruation which usually occurs between the ages of 10-16 years or in early adolescence in the middle of puberty before entering the reproductive period. World Health Organization in 2018, the age of adolescents ranges from 10-19 years, with an average age of menarche of 13 years. Nationally, the average age of menarche is 13-14 years, occurring in 37.5% of Indonesian teenagers, with the earliest occurrence being less than 9 years of age or later up to 17 years of age. The type of research used is analytical using secondary data. The sampling technique used total sampling, that is, the entire population was sampled as 35 teenagers experiencing menarche. Data processing starts from editing, coding, and tabulating. From the research results, it is known that 35 teenagers experienced menarche, based on the majority's knowledge, 15 respondents had insufficient knowledge (42.9%), 10 respondents (28.6%) had sufficient knowledge, 15 respondents based on the majority's age were 11-13 years old. (42.9%) minorities aged <13 years were 10 respondents (28.6%), based on the majority environment, the family environment was 15 respondents (42.9%) minorities from the non-school environment were 10 respondents (28.6%), based on the majority of information sources were family/friends as many as 15 respondents (42.9%) and the minority were mass media as many as 10 respondents (28.6%). From the research results, it was found that there was a relationship between young women's knowledge about menarche at SMPN 1 Panyabungan Selatan with a p-value of 0.001<0.05.